UNDERSTANDING OF CLIMATE CHANGE DISASTER RISK, AND VULNERABILITY AMONG STUDENTS, TEACHERS, AND ROLE- TAKERS - Vidal, Joshua; Anglo-Ojeda, Ailyn Bucatan; Madera, Marlita V. (Jurnal Tatsqif, 2024)
This research examines the understanding of climate change, disaster risk, and vulnerability in educational contexts, encompassing students, teachers, school administrators, and leaders in the selected schools in the Philippines. Utilizing a descriptive research design and surveys, the study reveals that both Basic Education (BE) and Senior High School (SH) students demonstrated notable comprehension of climate change, disaster risk exposure, and vulnerability, with SH students displaying slightly elevated understanding in specific areas. The findings emphasized the need to enhance disaster preparedness education for teachers and augment the grasp of climate change among school administrators. Furthermore, a strong positive correlation emerges between comprehending climate change and reducing vulnerability to disasters. In conclusion, this research underscores the urgency of bolstering understanding and preparedness related to climate change and disaster risks among students, educators, and educational leaders, necessitating dynamic educational strategies, collaboration with experts, and proactive measures to cultivate safety and resilience in the face of these multifaceted challenges.